KEANEKARAGAMAN IKAN SUNGAI KAMPAR INVENTARISASI DARI SUNGAI KAMPAR KANAN - Ronal Yuriza Fithra; Yusni Ikhwan Siregar (Jurnal Ilmu Lingkungan, 2010)
A study on fish biodiversity of Kampar River has been conducted. The study aimed at evaluatingthe existence of inhabiting fish species in the river and tributaries, in response to frequentdisturbance of water quality and quantity regime, due to anthropogenic factors. It revealed thatfish community found comprises of 9 ordo, 23 family, 40 genus, and of 58 species. Fish of familyCyprinidae, Bagridiae and Siluridae, were dominant in all sampling area with 25, 4 and 4species, respectively.